Analisis Deskriptif Produksi Jagung di Nusa Tenggara Timur - Marchy Pallo (Partner, 2020)
Corn is a commodity that plays a role in supporting food security other than rice and soybeans. Corn is not only used as raw material for the food and beverage industry, but also as animal feed ingredients. Factors affecting maize production in East Nusa Tenggara are fertilizers, pesticides, planting and cultivation patterns, formal education levels. The role of agricultural extension is very important because it is through them that renewable knowledge and technology can be distributed to local farmers. This is what can support East of Nusa Tenggara to become a corn center and become a province that contributes to Indonesia through self-sufficiency in corn food. South of Central Timor (TTS) can be used as a pilot district in increasing corn production.